The Kostant partition functions for twisted Kac-Moody algebras - Ranabir Chakrabarti; Thalanayar S. Santhanam (International Journal of Mathematics and Mathematical Sciences)
Employing the method of generating functions and making use of some infinite product identities like Euler, Jacobi's triple product and pentagon identities we derive recursion relations for Kostant's partition functions for the twisted Kac-Moody algebras.